2015
DOI: 10.1111/add.12972
|View full text |Cite
|
Sign up to set email alerts
|

Are predictors of making a quit attempt the same as predictors of 3-month abstinence from smoking? Findings from a sample of smokers recruited for a study of computer-tailored smoking cessation advice in primary care

Abstract: While high motivation and determination to quit is necessary to prompt an attempt to quit smoking, demographic factors and level of nicotine dependence are more important for maintaining abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 29 publications
(48 reference statements)
8
55
0
3
Order By: Relevance
“…This study replicates prior reports of an association between smoking fewer cigarettes per day at baseline (Kale et al, 2015; Vangeli et al, 2011) in smokers without major psychiatric illness and superior baseline attentional performance in smokers with schizophrenia spectrum disorders (Culhane et al, 2008). A novel finding in this study was that reduction in withdrawal prior to the quit date was associated with abstinence.…”
Section: Discussionsupporting
confidence: 88%
“…This study replicates prior reports of an association between smoking fewer cigarettes per day at baseline (Kale et al, 2015; Vangeli et al, 2011) in smokers without major psychiatric illness and superior baseline attentional performance in smokers with schizophrenia spectrum disorders (Culhane et al, 2008). A novel finding in this study was that reduction in withdrawal prior to the quit date was associated with abstinence.…”
Section: Discussionsupporting
confidence: 88%
“…Existing measures of quitting expectancies have been shown to have adequate internal and concurrent validity (Dijkstra et al, 1996; Hendricks et al, 2009; Sirota et al, 2010; Kale et al, 2015; Abrams et al, 2011; Hendricks et al, 2011; Kahler et al, 2013; Eklund et al, 1997; Lee et al, 2014; Macnee & Talsma, 1995; McKee et al, 2005; Rohsenow et al, 2015). The internal and concurrent validity of the PRBQ in our study appears to be similar to or slightly higher than that of these other measures.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial conducted in general practice among smokers not ready to quit examined five expected advantages and four expected disadvantages of quitting. Only one advantage (more energy and alertness) and one disadvantage (loss of concentration) predicted future quit attempts, and none of the items predicted abstinence success among attempters (Kale et al, 2015). Another study of smokers not trying to quit found negative expectancies about abstinence predicted a quit attempt but not abstinence, and that positive expectancies predicted neither (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations